Evaluating acceptance of lateral wedge insoles for knee osteoarthritis in Saudi Arabia: a mixed-methods study - Al Assiri, Abdullah (2025)
Background: Knee osteoarthritis (KOA) is a degenerative cartilage condition marked by inflammation and mechanical processes. In Saudi Arabia (SA), one in ten older individuals suffer from it. KOA often leads to pain, functional limitations, reduced daily activities, and diminished quality of life. For those with medial knee osteoarthritis, lateral wedge insoles (LWI) can alleviate knee pain and enhance function. While LWI offers biomechanical and symptomatic benefits, the perspectives of Saudi KOA patients and physiotherapists on its clinical use are not well-understood. In addition, there is limited research on gait modification treatment for other types of KOA, especially regarding facilitators and barriers in the Saudi context.